2023
DOI: 10.1001/jama.2023.21019
|View full text |Cite
|
Sign up to set email alerts
|

Early and Empirical High-Dose Cryoprecipitate for Hemorrhage After Traumatic Injury

Ross Davenport,
Nicola Curry,
Erin E. Fox
et al.

Abstract: ImportanceCritical bleeding is associated with a high mortality rate in patients with trauma. Hemorrhage is exacerbated by a complex derangement of coagulation, including an acute fibrinogen deficiency. Management is fibrinogen replacement with cryoprecipitate transfusions or fibrinogen concentrate, usually administered relatively late during hemorrhage.ObjectiveTo assess whether survival could be improved by administering an early and empirical high dose of cryoprecipitate to all patients with trauma and blee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(14 citation statements)
references
References 32 publications
1
10
0
Order By: Relevance
“…The recently published CRYOSTAT-2 (Early Cryoprecipitate in Major Trauma Hemorrhage) Study randomized patients to standard resuscitation practices or standard practices plus empiric cryoprecipitate transfusion. 22 In this trial, no clinical benefit was seen in patients randomized to empiric transfusion. It is noteworthy that the median time from admission to first administration of cryoprecipitate was 68 min, with less than 70% of the intervention arm patients receiving cryoprecipitate within the study goal of 90 minutes from admission.…”
Section: Discussionmentioning
confidence: 80%
“…The recently published CRYOSTAT-2 (Early Cryoprecipitate in Major Trauma Hemorrhage) Study randomized patients to standard resuscitation practices or standard practices plus empiric cryoprecipitate transfusion. 22 In this trial, no clinical benefit was seen in patients randomized to empiric transfusion. It is noteworthy that the median time from admission to first administration of cryoprecipitate was 68 min, with less than 70% of the intervention arm patients receiving cryoprecipitate within the study goal of 90 minutes from admission.…”
Section: Discussionmentioning
confidence: 80%
“…Although PROPPR was conducted some time ago, trauma resuscitation continues to be an area of active research. There have been several large and important randomized trauma transfusion clinical trials since PROPPR, including the Prehospital Air Medical Plasma (PAMPer), 11 Control of Major Bleeding After Trauma (COMBAT), 12 Clinical Randomization of an Antifibrinolytic in Significant Hemorrhage-2 (CRASH-2), 13 CRYOSTAT-2, 14 and several more are currently in progress including Trauma Resuscitation With Low-Titer Group O Whole Blood or Products, 10 Trauma and Prothrombin Complex Concentrate 15 and type O whole blood and assessment of AGE during prehospital Resuscitation 16 trials. Rapid and accurate selection of patients for these regulated trials is of paramount importance, and critical to their success.…”
Section: Discussionmentioning
confidence: 99%
“…Over time, barriers to conducting high-quality research in emergency settings have been progressively addressed, including the implementation of exceptions from informed consent for emergency research and the incorporation of novel study designs. 9 10 Nevertheless, international teams aiming to address these priorities are likely to need to secure funding from various organisations and navigate diverse regulatory frameworks. Despite these challenges, this priority-setting exercise has set a definitive, patient-centred tone, providing a road map for researchers to enhance the treatment and outcomes for patients following major traumatic injuries.…”
Section: Discussionmentioning
confidence: 99%
“… 4 8 More recently, several international randomised controlled trials have been conducted and reported, evaluating interventions for the most severely injured patients in highly acute treatment settings. 9 10 These demonstrate that high-quality research in major trauma is feasible and effective, but qualitative research suggests contemporary studies may not encompass topics and outcomes valued by trauma patients. 11 There is now an urgent need to identify research priorities to ensure that funding and resources are directed towards areas deemed most important by trauma patients and their families.…”
Section: Introductionmentioning
confidence: 99%